PERUBAHAN SEBARAN SEL-SEL ASIDOFIL DAN BASOFIL HIPOFISA PENGARUH PEMBERIAN PASAK BUMI (Eurycoma longifolia Jack) - Pratomo, Hurip; Supriatna, Iman; Manalu, Wasmen; Winarto, Adi (LPPM Universitas Terbuka, 2011)
Pasak bumi is popular as an aphrodisiac in the traditional medical herb. Boiled drink water of the root powder of pasak bumi is believed can increase the secondary reproduction characters such as libido and the duration of erection. This article is part of the research report that focus on: the distribution of hypophysis acidophil and basophil cells caused of the pasak bumi optimal dose treatment. Research carried out in an experiment using Hemaktosilin Eosin(HE) staining method to study micromorphological distribution of the acidophil and basophil cells of the male rat hypophysis after pasak bumi treatment (the dose of 18 mg pasak bumi/200 g body weight during three days, and the control of 1 ml aquadest). Result of the research showed that: Basophyl cells increased significantly in the third days of pasak bumi administered. Meanwhile acidophyl cells decreased in the third days of pasak bumi administered.